Manufacturing Government Communication on Covid-19 A Comparative Perspective - Maarek, Philippe J. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents a comparative perspective on different government communication strategies to COVID-19 around the globe. Scholars from twenty parts of the world specialized in political and government communication analyze initiatives and methods of various governments' communicative responses to the pandemic. In their contributions to this volume, they examine a wide range of distinct attitudes and reactions facing the crisis. Today's omnidirectional contact allowed by social media, with its load of contradictory rumors and fake news, often obliterates the citizens' ability to comprehend reality. The book frames a broad canvas on how government communication may deal with that and manage similar crises - bound to happen as climate changes and war menaces are generating more and more worries about the future of humanity. This makes this volume a must-read for scholars and students of political communication, health policies and communication, crisis marketing and communication. It will also be of utmost interest for practitioners and policy-makers from these fields willing to better understand government communication and its answer to global crises.
Chapter 1. Similar and Dissimilar Patterns of Government Communication on COVID-19 -- Part I. Organizing Centralized Government Strategies -- Chapter 2. Pros and Cons of the Eu Response and Communication During COVID-19 Crisis -- Chapter 3. Fighting COVID-19 by State Mobilization: China in the Lens of Social Constructivism -- Chapter 4. Crisis Communication During the First Wave of the Pandemics: the Latvia's Case -- Chapter 5. South Korea: Positive to Negative Attention -- Chapter 6. No Lockdown, please, We Are Swedish: How the Middle Way Country Suddenly Became the Extreme Case of Government Communication -- Part II. Local Versus National -- Chapter 7. National Leadership Versus Regional Command: The Case of the Spanish COVID-19 Crisis -- Chapter 8. Rituals and Reassurance: Government Communication in Australia During the COVID-19 Pandemic -- Chapter 9. Efforts in Communicating Science in Brazil in a Context of a Denialist Government and Contradictory Realities -- Chapter 10. Government Communication Policy for Dealing with the COVID-19, the Case of Israel: How to Explain to Groups with Unique Communication Characteristics a Universal Phenomenon -- Part III. Taking the Leader's Way -- Chapter 11. "Trump Confronts COVID - in Press Briefings and on Twitter" -- Chapter 12. Between Empathy and Threat: Legitimation Strategies and Rhetorical Appeals in Angela Merkel's Response to the COVID-19 Pandemic -- Chapter 13. Italian Government Communication from Giuseppe Conte to Mario Draghi: Between 'permissive Consensus' and 'leadership Building' -- Part IV. The Weight of Government Credibility -- Chapter 14. The Greeks and the Coronavirus Pandemic: Assessing the Credibility and Effectiveness of Social Institutions and Public Sphere Players -- Chapter 15. The UK: 'not One Rule for Everyone' and the Impact of Elite Rule-breaking on Public Trust -- Chapter 16. The Messenger and the Message: South African Government Communication During the COVID-19 Pandemic -- Chapter 17. Pushing Through Own Agenda: COVID-19 and Government Communication in Poland -- Part V. The Importance of Social Media -- Chapter 18. Redefining the Citizen-government Relationship: Policy Communication Through Social Media in Post-COVID Japan -- Chapter 19. A Vos Seringues : French Governmental Communication on COVID-19 Vaccination via Twitter.
Keywords: Communication in politics; Comparative government; Political science; Mass media-Political aspects; Political Communication; Comparative Politics; Governance and Government; Media Policy and Politics